Feeling Guilty and Flattering God: The Mediating Role of Prayer. Issue 2 (June 2022) - Zarzycka, Beata; Tomaka, Kamil; Zając, Katarzyna; Marek, Klaudia
Ingratiation refers to acts of flattery, typically given by a low-power person to a high-power one, performed to gain acceptance and approval. This study investigates ingratiation in the religious setting, asking whether people feeling high levels of guilt or shame tend to manifest such ingratiating behavior toward God. The study aimed to examine the mediating role of prayer in the relationship between guilt and shame and ingratiation toward God. A total of 148 respondents (80 women and 68 men) participated in the study. The Religious Ingratiation Scale, the Content of Prayer Scale, and the Guilt and Shame Proneness Scale were applied to the research. The results showed that feeling guilty increased the tendency to ingratiation toward God. Prayer was the significant mediator in this relationship. People high in guilt tend to flatter God by offering more adoration and fewer repine prayers.